PERANCANGAN FASILITAS KERJA YANG ERGONOMIS DEPARTEMEN STORE PADA PT NOK FREUDENBERG SEALING TECHNOLOGIES - Butar Butar, Poltak Samuel; Sri Zetli (Computer Science and Industrial Engineering, 2025)
In the modern industrial era, ergonomic challenges have become increasingly critical, particularly in manual labor sectors that are highly prone to Musculoskeletal Disorders (MSDs). This study aims to design ergonomic work facilities in the Store Department of PT NOK Freudenberg Sealing Technologies, specifically for the pallet transfer process, which is still performed manually. The research methodology integrates the Nordic Body Map (NBM) for identifying MSD complaints, the Rapid Entire Body Assessment (REBA) for evaluating working postures, and the Ergonomic Function Deployment (EFD) for developing ergonomic solutions. The study involved three workers, selected using a saturated sampling technique due to the small population. NBM questionnaire results indicated high levels of physical discomfort, especially in the shoulders, back, and knees. REBA assessments revealed an average risk score of 7, categorized as high, indicating the urgent need for intervention. The ergonomic table was designed based on workers’ anthropometric data and the ENASE ergonomic aspects (Effective, Comfortable, Safe, Healthy, Efficient). The proposed design successfully reduced the REBA score 7, demonstrating a significant improvement in work safety and comfort. This study concludes that applying ergonomic design based on anthropometric data and the EFD method effectively reduces the risk of injury caused by poor working posture, while enhancing efficiency and worker well-being in industrial environments